1986
DOI: 10.1007/bf00197025
|View full text |Cite
|
Sign up to set email alerts
|

Water permeability of plant cuticles: permeance, diffusion and partition coefficients

Abstract: Summary. Using isolated cuticular membranes from ten woody and herbaceous plant species, permeance and diffusion coefficients for water were measured, and partition coefficients were calculated. The cuticular membranes of fruit had much higher permeance and diffusion coefficients than leaf cuticular membranes from either trees or herbs. Both diffusion and partition coefficients increased with increasing membrane thickness. Thin cuticles, therefore, tend to be better and more efficient water barriers than thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
101
2
2

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(110 citation statements)
references
References 15 publications
5
101
2
2
Order By: Relevance
“…Becker, Kerstiens & Schonherr (1986) reported a value of 4-3 //m for the gravimetrically determined thickness of isolated ivy cuticle. The cuticle of the mature ivy leaf is much thinner than that of Lycopersicon esculentum fruit (14-2 //m) or Buxus sempervirens leaf (ll-2//m) (Chaumat & Chamel, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Becker, Kerstiens & Schonherr (1986) reported a value of 4-3 //m for the gravimetrically determined thickness of isolated ivy cuticle. The cuticle of the mature ivy leaf is much thinner than that of Lycopersicon esculentum fruit (14-2 //m) or Buxus sempervirens leaf (ll-2//m) (Chaumat & Chamel, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…It may be that fruit cuticle does not need to be as dynamically regulated by water stress as the leaf cuticle, since the surface/volume ratio of leaves is far higher than that of fruits and the leaves have stomata, both of which are factors that make leaves more prone to desiccation. Moreover, fruit cuticles of various species are, on average, thicker than leaf cuticles, but are also more permeable (Becker et al, 1986;Araus et al, 1991;Schreiber and Riederer, 1996), suggesting that limiting water loss is more important in leaves than in fruits. Indeed, it has been suggested that transpirational water loss may be necessary for fruit growth (Lee, 1989;Schreiber and Riederer, 1996).…”
Section: Aba Deficiency Has Distinctly Different Effects On Tomato Frmentioning
confidence: 99%
“…the more surface water, the more capacity for sorbing HNOg vapour). Data on the thickness of leaf water films is not available but experimental data has shown that ambient vapour pressures lead to variable levels of surface hydration (Chamel et al, 1991) which have been shown to impact the rate of water and ion permeability of cuticles (Becker, Kerstiens & Schonherr, 1986;Berg, 1987). Furthermore, Cadle et al (1991) reported that surface accumulation of HNOg derived nitrate is greater for leaves exposed under 34 versus 27% relative humidity.…”
Section: A Generalized Leaf-level Model Of Hno^ Vapour Depositionmentioning
confidence: 99%